EDUKASI DAGUSIBU DALAM RANGKA HARI FARMASIS SEDUNIA DI DESA MAJU MAKMUR TANAH BUMBU - Mahdi, Nur; Maghfirah, Rahmayani; Alawiyah, Tuty (Jurnal Bakti untuk Negeri, 2024)
DAGUSIBU plays a pivotal role in effective therapy and disease management. However, it is disheartening to observe that a significant portion of the population remains uninformed about proper medication practices. This lack of understanding poses severe health risks and hinders the healing process. This initiative aims to empower community members as household medication educators, equipping them with the knowledge and skills to effectively obtain, utilize, store, and dispose of (DAGUSIBU) medications. The methodology encompasses careful planning, preparation, comprehensive education, and thorough evaluation. The post-test results revealed a remarkable 69% increase in DAGUSIBU knowledge among the participants. 31% of the participants were categorized as 'good' in their understanding, while the remaining 69% fell under the 'sufficient' category. These findings unequivocally demonstrate a substantial improvement in the knowledge base of the RT. 2 Desa Maju Makmur community. Armed with adequate knowledge and understanding, individuals are better equipped to make informed decisions regarding medication use, ensuring their own well-being and that of their families. By promoting responsible medication practices, we can collectively safeguard public health and foster a healthier society.